PELATIHAN ASESMEN DALAM KURIKULUM MERDEKA DI YAYASAN MIFTAHUL HUDA KECAMATAN BUMI AGUNG KABUPATEN LAMPUNG TIMUR - Nur Indah Sari; Laila Nursafitri (LPPM STAI DARUSSALAM LAMPUNG, 2023)
The implementation of community service activities (PKM) aims to provide training to RA, MI, MTs, and MA teachers at the Miftahul Huda Foundation, Bumi Agung District, East Lampung Regency regarding assessment in the independent curriculum. This activity is carried out through expository and discussion methods. This activity consists of: (1) presenting the flow of understanding the independent curriculum; (2) presentation of material regarding assessment in the independent curriculum; (3) discussion; and (4) activity evaluation. The number of activity participants is as many as 20 teachers who teach various subjects. The response given by the service partners was very good, so that this service activity could be carried out smoothly and the participants were actively involved in discussion and question and answer activities. The results obtained from the PKM activities are that the teacher's knowledge and understanding of the independent curriculum and the assessment or evaluation contained in the independent curriculum increases, so that teachers can better prepare and carry out this curriculum. Merdaka curriculum can run well in schools. However, various seminar, training and workshop programs need to be continuously improved to strengthen teacher knowledge and skills in implementing the independent curriculum, especially at the student learning assessment stage.